Asymmetric multi-component trifunctionalization reactions with α-Halo Rh-carbenes - Xiaoyan Yang; Xiaoyu Zhou; Wenhao Hu; Yu Qian (Nature Communications)
Abstract Multi-component multi-functionalization reactions involving active intermediates are powerful tools for rapidly generating a wide array of compounds. Metal carbynoids, with their distinct reactivity, hold great promise for developing synthetic methodologies. However, their application in catalytic transfer reactions has been hindered by the limited availability of suitable precursors. In this study, we investigate the catalytic potential of α-halo Rh-carbenes, leveraging the concept of metal carbynoids in multi-functionalization reactions. Through a chiral phosphoric acid-catalyzed asymmetric trifunctionalization, we have developed a method for synthesizing a variety of chiral α-cyclic ketal β-amino esters with high yields and excellent enantioselectivity. Our extensive experimental and computational studies reveal that α-halo Rh-carbenes exhibit carbynoid properties, which facilitate the transformation into functionalized Fischer-type Rh-carbenes through the decomposition of the C-halo bond.